Isolation and molecular characterization of mycotoxigenic fungi from Palm Kernel Cake and effects of temperature on aflatoxin production - Razali, Siti Mardhiyah (2016)
The widespread contamination of animal feed with mycotoxin is not a new issue worldwide. This toxin is produced by mycotoxigenic fungi as secondary metabolites and it is harmful to human and animal. Apart from economic lost; the mycotoxin can have adverse health effects to humans due to the carcinogenicity, teratogenicity, and mutagenicity potentials of the toxins. Palm Kernel Cake (PKC) is the largest animal feed production in Malaysia. PKC is a by-product of palm kernel oil processing and it has been exported as animal feed. The improper storage facilities for PKC may lead to conditions which enhance the aflatoxigenic fungi growth and thus the production of aflatoxins in PKC. The purpose of this study is to isolate and characterize toxigenic fungi from PKC, to determine the effect of media and temperatures on the fungal growth, and to study the effect of PKC storage temperatures on aflatoxins production. For the first objective, characterization of fungi was conducted by using 3 different media culture; Dichloran Rose Bengal Chloramphenicol (DRBC) Agar, Dichloran 18% Glycerol (DG18) Agar and Malt Extract Agar (MEA) from PKC that is stored under 3 different temperatures of 4˚C, 25˚C and 60˚C. Identification of fungi was carried out based on macroscopy and microscopy as well as molecular identification. Incidences of four mycotoxigenic fungi were found from PKC (Aspergillus niger, Aspergillus flavus, Aspergillus fumigatus and Penicilium citrinum). In order to characterize polymorphism of the isolates, RAPD assay was performed by using OPA 3 as the primer. A dendogram was generated by GelCompare 4.2 software. The dendogram tree was clustering based on the amplified segments grouped the isolates according to their treatments of temperature and media culture. The identification of the isolates are obtained based on the banding pattern from the generated dendogram. The software resulted in constructed dendogram to reveal the percentage of similarities between the typable isolates (A. fumigatus, A. niger and P. citrinum) within ranged from 20% to 80%. The effect of storage temperature on the strains enumeration is reported through this work. The distributing strains are influenced by the storage temperature of PKC matrices. The findings clearly viewed that Aspergillus species profused at 25⁰C PKC storage while it is restricted at low and high temperature. The validated HPLC method for detection of aflatoxins from spiked PKC with A. flavus was greatly evaluated. Acceptability of linearity of this methods was achieved with correlation coefficients of linear range of 0.998 (AFB1), 1 (AFB2), 0.9987 (AFG1) and 0.999 (AFG2). A good recovery also found within ranged 82.5% to 102.8%. The findings however showed no aflatoxin detected at any of incubated temperature of PKC from day 0 until the day of 28. Therefore, another experiment is conducted to detect the availability of the toxins in the selected isolate of A. flavus. As expected, there are no aflatoxins recognized from the strain. This finding suggested that the isolated A. flavus species was not associated with aflatoxin producing eventhough it was under the favorable condition for fungi growth. In conclusion, the collected PKC is free with aflatoxigenic strains thus the risk to be contaminated by aflatoxins is low.